Pengalaman Adaptasi Antarbudaya Mahasiswa Perantau di Kota Kupang - Antonia Bara Benge Tani; Petrus Ana Andung; Ferly Tanggu Hana (Jurnal Communio : Jurnal Jurusan Ilmu Komunikasi, 2019)
This study aims to describe the communication experience of Manggarai students when adapting to students from Kota Kupang at Nusa Cendana University and to analyze the strategies / stages that students go through and to find out and analyze the meanings of Manggarai students about the status of migrant students in Kupang City. This study uses the phenomenology method with the reason that this research departs from phenomena or experiences that occur in everyday life. By using potential informants as data sources, in this study the data is presented through in-depth interviews and non-participant observation. The data analysis technique used is data reduction, data presentation, and conclusions / verification. This study uses the Accommodation Theory of Communication and Phenomenology Theory as a reference for data analysis. The results of the study based on the Communication Accommodation Theory that from communication experience revealed that, students from Manggarai who were studied conducted convergence by learning to use the dialect and the Kupang language. This is done in order to create effective communication where, the mutual understanding between communicators and communicants. Not only that, students from Manggarai also began to build social intimacy with Kupang City students. In addition, the form of strategies / stages of cultural adaptation carried out by students from Manggarai are students from Manggarai studied doing strategies or stages classified in the Readjustment stage (adaptation phase), and Resolution (resolution / adjustment phase), based on resolution or the final results carried out by Manggarai students were, full participation, where they began to be friends with Kupang City students, and acted as if they were students from Kupang City. Finally, the meaning of students from Manggarai about the status of migrant students in Kota Kupang is based on the Phenomenology Theory in which the knowledge underlying the meaning is obtained through direct experience of students from Manggarai, namely: migrant students as change makers for a better life in the future, and migrant students as science fighter.